Faktor yang berhubungan dengan kejadian obesitas pada masa pandemi Covid-19 - Herlina Anggraini; Setiawati Setiawati; Rilyani Rilyani (Holistik Jurnal Kesehatan, 2022)
Background: Obesity is the accumulation of excess fat due to an imbalance in energy intake (energy intake) with energy used (energy expenditure). Obesity and overweight are two different things, but both of them show the presence of excess fat accumulation in the body which is indicated by an increase in body mass index (BMI) above normal as measured using the formula of body weight (Kg) divided by height (m²). The incidence of obesity in Malahayati University students in 2019 with data on obese students as many as 60 (34%) from 175 students with research results there is a relationship between sleep patterns and junk food on the obesity level of Malahayati University students in Bandar Lampung.Purpose: Known factors related to obesity during the Covid-19 pandemic to the incidence of obesity in students at the Faculty of Medicine, Malahayati University, Bandar Lampung.Method: type of quantitative research with cross sectional approach design. The sampling technique used was the quota sampling technique. The population in this study were students of the Faculty of Medicine of the Nursing Science Study Program who had a history of obesity with a total of 175 students at Malahayati University, Bandar Lampung. Measurement using a questionnaire and analyzing data using chi-square.Results: Of the chi square test show that the obesity factors that are significantly related and become a factor in the occurrence of obesity in students are the genetic factor of the student's father (p-value = 0.42; OR = 2.444); mother (p-value = 0.000; OR = 28,000); consumption of fast food (p-value = 0.000; OR = 21,500); physical activity (p-value = 0.000; OR = 2,032). Students who have obese parents have a higher risk of obesity, frequent fast food consumption and light physical activity factors are 3 times more likely to be at risk of obesity than students who do moderate physical activity.Conclusion: There is a relationship between genetic factors, diet and physical activity of students with the incidence of obesity in students. Keywords: Genetic; Dietary; Physical Activity; Obesity; Covid-19 PandemicPendahuluan: Obesitas merupakan penumpukan lemak yang berlebih akibat ketidak seimbangan asupan energi (energy intake) dengan energi yang digunakan (energy expenditure). Obesitas dan overweight adalah dua hal yang berbeda namun keduanya sama-sama menunjukkan adanya penumpukan lemak yang berlebih dalam tubuh yang ditandai dengan peningkatan indeks masa tubuh (IMT) di atas normal yang diukur menggunakan rumus berat badan (Kg) dibagi tinggi badan (m²). Kejadian obesittas pada mahasiswa Universitas Malahayati tahun 2019 dengan data mahasiswa obesitas sebanyak 60 (34%) dari 175 responden dengan hasil penelitian terdapat hubungan antara pola tidur dan makanan junk food pada tingkat obesitas mahasiswa Universitas Malahayati Bandar Lampung.Tujuan: Diketahui faktor-faktor yang berhubungan  dengan obesitas selama masa pandemi Covid-19 terhadap kejadian Obesitas pada mahasiswa di Fakultas Kedokteran Universitas Malahayati Bandar Lampung.Metode: jenis penetian kuantitatif dengan desain pendekatan cross sectional. Teknik pengambilan sampel menggunakan teknik jenis sampling kuota. Populasi pada penelitian ini adalah mahasiswa fakultas Kedoteran Prodi Ilmu Keperawatan yang memiliki riwayat obesitas dengan jumlah 175 responden di Universitas Malahayati Bandar Lampung. Pengukuran menggunakan kuesioner dan menganalisa data menggunakan chi-square.Hasil: Dari uji chi square menunjukan faktor-faktor obesitas yang secara signifikan hubungan dan menjadi faktor  terjadinya obesitas pada mahasiswa adalah faktor genetik ayah mahasiswa (p-value = 0,42; OR = 2,44); ibu (p-value = 0,000; OR = 28,000); konsumsi fast food (p-value = 0,000; OR = 21,500); aktifitas fisik (p-value = 0,000; OR 2,032). Mahasiswa yang memiliki orang tua yang gemuk memiliki risiko lebih tinggi mengalami obesitas, konsumsi fast food yang sering dan faktor aktifitas fisik  yang ringan memiliki kemungkinan 3 kali lebih berisiko mengalami obesitas berisiko dibandingkan dengan mahasiswa yang melakukan aktifitas fisik sedang.Simpulan: Terdapat hubungan faktor genetik, pola makan dan aktifitas fisik mahasiswa dengan kejadian obesitas mahasiswa.